PENGARUH CITRA MEREK, KEPERCAYAAN MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELI DALAM MEMBELI PRODUK KOSMETIK MAKE OVER DI BATAM - -, Angelica; Hikmah, Hikmah (SCIENTIA JOURNAL, 2025)
This study aims to analyze the influence of Brand Image, Brand Trust, and Product Quality on the Purchase Decision of Make Over cosmetic products in Batam. This research uses a quantitative method with a survey approach through a questionnaire distributed to 204 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with the help of SPSS version 25. The results show that Brand Image (β=0.416, t=5.008, p<0.001), Brand Trust (β=0.135, t=1.981, p=0.049), and Product Quality (β=0.201, t=3.648, p<0.001) have a positive and significant partial effect on the Purchase Decision. Simultaneously, all three variables have a significant effect with an F value of 47.963 (p<0.001) and can explain 41.0% of the variation in purchase decisions. These findings indicate that consumers are more likely to purchase Make Over products when they have a positive perception of the brand, trust the quality, and believe the products meet high-quality standards. The results of this study provide implications for Make Over's marketing strategy to increase its market share in Batam by optimizing Brand Image, building consumer trust, and maintaining product quality